Effectiveness of Counseling to Increase Knowledge and Lower Blood Sugar Levels of Diabetes Mellitus Patients in Tompotikka Sub-district - Harliani Harliani; Baharuddin Korja (Humanistic Network for Science and Technology (HNST), 2018)
There has been a growing perception in the community that a person has diabetes mellitus because one of his parents suffers from the disease. This experimental study provided a counseling about diabetes mellitus with the aim of increasing public knowledge about diabetes mellitus. It was expected that increased knowledge will change the pattern of life for the better, so that blood sugar could be controlled. Before the treatment was done pre-test and blood glucose measurement, while after the treatment was done post-test and the measurement of blood sugar level again. From the results of pre-test it appears that public knowledge about DM was still low. Post-test results showed that people's knowledge about all factors related to diabetes mellitus has increased. Meanwhile, the time span about one month after the implementation of counseling had managed to lower blood sugar from most respondents. Keywords: Diabetes mellitus, Blood sugar, Counseling, Knowledge